Hubungan Status Anemia, Kualitas Tidur, dan Kemampuan Kognitif pada Remaja Putri Usia 12-24 Tahun di Indonesia (Analisis Data Indonesian Family Life Survey (IFLS) 5): Hubungan Status Anemia, Kualitas Tidur, dan Kemampuan Kognitif pada Wanita Muda Usia 15-24 Tahun di lndonesia (Analisis Data Indonesian Family Life Survey (IFLS) 5) - Helmyati, Siti; Fauziah, Lutfi Afida; Kadibyan, Pinaes; Sitorus, Nova Lidia; Dilantika, Charisma (Universitas Airlangga, 2023)
Background: Anemia is still one of the nutrition problems in Indonesia. Women of reproductive age, including the age group 15-24 years, is a group with higher risk of anemia. Iron deficiency anemia is a common cause of anemia. Iron is one of the micronutrients that important for the body, including brain. Some studies suggest that iron deficiency is associated with sleep quality and cognitive ability. Iron has a complex effect on the dopaminergic system by being a cofactor of tyrosine hydroxylase which is part of dopamine D2 receptor function. Neuromodulation by the dopaminergic system plays an important role in sleep regulation. It can also interfere with the brain's ability to spread nerve impulses that have potential to cause several disorders, one of which is motor and cognitive disorders. Objectives: This study aims to determine the relationship of anemia status with sleep quality and cognitive abilities in young women aged 15-24 years in Indonesia based on IFLS 5. Methods: This study used cross sectional design and secondary data from IFLS 5 with subjects totaling 2016 young women aged 15-24 years. This study used chi-square as statistical test with significance level p<0.05. Results: The prevalence of anemia in young women aged 15-24 years was 39.93%. It was found that there was no relationship between anemia status and sleep quality consisting of sleep disturbance (p=0.624) and sleep quality (p=0.693) and there was no relationship between anemia and cognitive ability (p=0.702). Conclusions: Anemia status has no significant relationship with sleep quality and cognitive ability.